Leaf color change and photosystem function evaluation under heat treatment revealed the stress resistance variation between Loropetalum chinense and L. chinense var. rubrum - Cai, Wenqi; Zhang, Damao; Zhang, Xia; Chen, Qianru; Liu, Yang; Lin, Ling; Xiang, Lili; Yang, Yujie; Xu, Lu; Yu, Xiaoying; Li, Yanlin (PeerJ, 2023)
This research mainly focused on the leaf color change and photosystem function differentiation between Loropetalum chinense and its variety L. chinense var. rubrum under heat stress, which were tightly concerned about their ornamental traits and growth. L. chinense ‘Xiangnong Xiangyun’ (X) and L. chinense var. rubrum ‘Xiangnong Fendai’ (F) and L. chinense var. rubrum ‘Hei Zhenzhu’ (H) were chosen to be experimented on to investigate whether leaf color morphology and pigment composition could influence the adaptability of plants to high temperature in order to select foliage plants which posses stable leaf color and better adaptability for hot regions. The plants were cultured in hot environment (40 °C/33 °C, day/night) and normal environment (25 °C/18 °C, day/night). Phenotype and anatomic observation of three cultivars were made and leaf color indices and pigment contents were measured. During the experiment, H and F gradually turned green, total anthocyanins contents significantly decreased in them, however, chlorophyll b contents increased in all three cultivars. In addition, the initial fluorescence (Fo) decreased in X, while increased in H and F. For the maximum fluorescence (Fm) and maximum photochemical efficiency of PSII (Fv/Fm), they only increased in H and decreased in both F and X. The non-photochemical chlorophyll fluorescence quenching (NPQ) also increased in H and decreased in F. For X, it increased at first then gradually decreased. The coefficient of photochemical quenching all increased at first then gradually decreased. Correlation analysis between showed that there was relatively strong connection between anthocyanins, flavonoids and chlorophyll fluorescence parameters, especially NPQ, proved anthocyanins and flavonoids might not only involved in enriching leaf color, but also interfered with the protection of photosystem. Generally speaking, we found higher anthocyanin and flavonoids content level not only dramatically enriched the leaf color of L. chinense var. rubrum cultivars, but also offered more potential antioxidant to keep their normal growth when encountered heat stress.
Keywords: Heat stress; Leaf color; Photosystem function; Loropetalum chinense var. rubrum